2020
DOI: 10.1007/s10955-020-02636-7
|View full text |Cite
|
Sign up to set email alerts
|

Sunklodas’ Approach to Normal Approximation for Time-Dependent Dynamical Systems

Abstract: We adapt Stein's method to obtain Berry-Esseen type error bounds in the multivariate central limit theorem for non-stationary processes generated by timedependent compositions of uniformly expanding dynamical systems. In a particular case of random dynamical systems with a strongly mixing base transformation, we derive an error estimate of order O(N −1/2 ) in the quenched multivariate CLT, provided that the covariance matrix "grows linearly" with the number of summands N . The error in the normal approximation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…A similar condition was introduced by Leppänen in [Lep17] and further studied by Leppänen and Stenlund in [LS17,LS20]. In particular, [Lep17] showed that functional correlation decay implies a multi-dimensional CLT with bounds on the rate of decay.…”
Section: Resultsmentioning
confidence: 68%
“…A similar condition was introduced by Leppänen in [Lep17] and further studied by Leppänen and Stenlund in [LS17,LS20]. In particular, [Lep17] showed that functional correlation decay implies a multi-dimensional CLT with bounds on the rate of decay.…”
Section: Resultsmentioning
confidence: 68%
“…ω ∈ Ω and φ ∈ BV . The conclusion of the lemma now follows readily from (37) and the triangle inequality.…”
Section: Twisted Transfer Operatorsmentioning
confidence: 78%
“…Among many remarkable contributions, we particularly emphasize those dealing with the decay of correlations [2,6,7,9,12,15], various (quenched or annealed) limit laws [1,4,16,17,18,19,20,30,31,32,39,43,44,48], as well as recent results devoted to the linear response of random dynamical systems [8,23,47]. For similar results in the closely related context of sequential dynamical systems, we refer to [10,11,33,35,36,37,29,42] and references therein.…”
Section: Introductionmentioning
confidence: 98%
“…for P-a.e. ω ∈ Ω, where t T denotes the transpose of t. Substituting θ = t/ √ n in (33) and taking into account…”
Section: Central Limit Theoremmentioning
confidence: 99%
“…Furthermore, we mention the recent interesting papers by Bahsoun and collaborators [2,4,5] as well as Su [43] concerned with the decay of correlation and limit laws for systems which can be modelled by random Young towers. Further relevant contributions to the study of statistical properties of random or time-dependent dynamics have been established by Nándori,Szász,and Varjú [38], Nicol, Török and Vaienti [39], Hella and Stenlund [28], Leppänen and Stenlund [32,33] as well as the second author [25,26].…”
Section: Introductionmentioning
confidence: 99%